Profil Farmakokinetik Senyawa Flavonoid Ekstrak Metanol Bunga Telang (Clitoria ternatea.L) Pada Kelinci (Oryctolagus cuniculus) Menggunakan High-Performance Liquid Chromatography - Widy Susanti Abdulkadir; Faramita Hiola; Dizky Ramadani Putri Papeo; Endah Nurrohwinta Djuarno; Rahmat Hidayat Domili (Universitas Negeri Gorontalo, 2026)
Butterfly pea (Clitoria ternatea L.) is a climbing plant known for its medicinal properties and contains bioactive compounds such as tannins, carbohydrates, saponins, triterpenoids, polyphenols, flavanol glycosides, proteins, alkaloids, anthraquinones, anthocyanins, stigmasterol-4-ene-3,6-dione, volatile oils, and steroids. This study aimed to determine the pharmacokinetic profile—Area Under the Curve (AUC), maximum concentration (Cmax), time to reach maximum concentration (Tmax), half-life (t½), elimination rate constant (Ke), absorption rate constant (Ka), clearance (Cl), and volume of distribution (Vd)—of flavonoid compounds from the methanolic extract of butterfly pea (Clitoria ternatea L.) in rabbit plasma using a time-series experimental design.Two rabbits were fasted for 12 hours, then administered a positive control dose of 16.05 mg/kg and an extract dose of 5.952 mg orally. Blood samples were collected at 0, 1, 2, 4, 6, 12, and 24 hours after administration, and plasma concentrations were analyzed using HPLC with quercetin as the standard. The results showed that flavonoid compounds were detected in plasma with an AUC of 633.316 µg·h/mL, Cmax of 20.59 µg/mL, Tmax of 4 hours, t½ of 22.5 hours, Ka of 0.7202/h, Ke of 0.03375/h, and Vd of 48.451 mL.